Combination of ERG9 Repression and Enzyme Fusion Technology for Improved Production of Amorphadiene in Saccharomyces cerevisiae - Rama Raju Baadhe; Naveen Kumar Mekala; Sreenivasa Rao Parcha; Yalavarthy Prameela Devi (Journal of Analytical Methods in Chemistry)
The yeast strain (Saccharomyces cerevisiae) MTCC 3157 was selected for combinatorial biosynthesis of plant sesquiterpene amorpha-4,11-diene. Our main objective was to overproduce amorpha 4-11-diene, which is a key precursor molecule of artemisinin (antimalarial drug) produced naturally in plant Artemisia annua through mevalonate pathway. Farnesyl diphosphate (FPP) is a common intermediate metabolite of a variety of compounds in the mevalonate pathway of yeast and leads to the production of ergosterols, dolichol and ubiquinone, and so forth. In our studies, FPP converted to amorphadiene (AD) by expressing heterologous amorphadiene synthase (ADS) in yeast. First, ERG9 (squalane synthase) promoter of yeast was replaced with repressible methionine (MET3) promoter by using bipartite gene fusion method. Further to overcome the loss of the intermediate FPP through competitive pathways in yeast, fusion protein technology was adopted and farnesyldiphosphate synthase (FPPS) of yeast has been coupled with amorphadiene synthase (ADS) of plant origin (Artemisia annua L.) where amorphadiene production was improved by 2-fold (11.2 mg/L) and 4-fold (25.02 mg/L) in yeast strains YCF-002 and YCF-005 compared with control strain YCF-AD (5.5 mg/L), respectively.